Relative superiority of Boer x Kacang goats at pre-weaning - Mahmilia, Fera Mahmilia; Doloksaribu, Meruwald (Indonesian Animal Sciences Society, 2010)
productivity expected from these crosses is the effect of heterosis or hybrid vigor. Boer goat is selected to improve the productivity of local Kacang goats, because this goat has a high genetic potential and has a large body formation. The objective of this research was to evaluate relative superiority of crossbreed between Boer and local goat (Kacang) during pre weaning period. The research was conducted at Goat Research Station, Sei Putih-North Sumatra, from Januari 2007 to December 2009. During pre weaning period the kids were reared with their mothers in group pen. Research results showed that birth weight and weaning weight of crossbreds (Boerka 1 and Boerka 2) were heavier than that of Kacang goat. The relative superiority of the crossbreds were 21,89 - 43,20% for birth weight, 32,88 â 54,68% for weaning weight and 37,11 â 53,32% for pre weaning daily gain. In addition the degree of mortality at pre weaning period of crossbreeds was lower than that of Kacang goats. Key words: Kacang Goat, Boer, Boerka, Relative Superiority